2022
DOI: 10.5051/jpis.2200960048
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of implant-abutment connection type on marginal bone loss and survival of dental implants

Abstract: Purpose This study aimed to compare the long-term survival rate and peri-implant marginal bone loss between different types of dental implant–abutment connections. Methods Implants with external or internal abutment connections, which were fitted at Gangneung-Wonju National University Dental Hospital from November 2011 to December 2015 and followed up for >5 years, were retrospectively investigated. Cumulative survival rates were evaluated for >5 years, and peri-implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
1
7
1
Order By: Relevance
“…Data obtained in the present study indicated that cementretained prostheses were significantly more prone to develop higher MBL than screw-retained ones. This corroborates emerging evidence suggesting that the presence of undetected subgingival cement remnants can lead to increased MBL which in turn may trigger the onset of peri-implantitis (Kim et al, 2022;Staubli et al, 2017).…”
Section: Maiorana Et Al Demonstrated the Importance Of The Passivationsupporting
confidence: 89%
“…Data obtained in the present study indicated that cementretained prostheses were significantly more prone to develop higher MBL than screw-retained ones. This corroborates emerging evidence suggesting that the presence of undetected subgingival cement remnants can lead to increased MBL which in turn may trigger the onset of peri-implantitis (Kim et al, 2022;Staubli et al, 2017).…”
Section: Maiorana Et Al Demonstrated the Importance Of The Passivationsupporting
confidence: 89%
“…Concerning the type of implant connection, a recent study (19) showed no significant difference in the cumulative survival rate between implants with external and internal abutment connections. These results seem to corroborate the findings of the present study.…”
Section: Discussionmentioning
confidence: 95%
“…Secondly, the study examined only a small subset of enamel matrix derivative concentrations, which may not accurately reflect the full range of effective amounts [ 52 ]. The study tracked cell behavior for up to 14 days only, which may not accurately represent how the enamel matrix derivative will affect the cells over the long run [ 53 ]. It would also be helpful to investigate the effectiveness of enamel matrix derivative at various concentrations and exposure times.…”
Section: Discussionmentioning
confidence: 99%